Analysis of Migration Factors Case Study: Samangan Province (Salam International Academic Journal, 2025)
The primary objective of this research is to identify and analyze the economic, security-related, cultural, and environmental factors influencing migration in Samangan Province, as well as their effects on the region's social and economic conditions. This study aims to gain a deeper understanding of the reasons behind the migration of the people of Samangan to foreign countries. Migration, as a socio-economic phenomenon, is increasingly prevalent in many parts of Afghanistan, including Samangan.This rise in migration can be attributed to economic, social, cultural, geographical, natural, or political challeges. Therefore, a detailed examination of these factors and their impact on both migrant and non-migrant communities is essential for strategic policymaking aimed at improving the region’s situation.A field research method was employed in this study. Data were collected through research questionnaires distributed among local residents and social experts. Additionally, statistical techniques and qualitative content analysis were employed to assess the impact of various migration drivers such as unemployment, poverty, lack of public services, and social problems.The findings of the research show that the main migration factors in Samangan include:Economic issues and unemploymentLack of job and educational opportunitiesSocial challengesAbsence of basic infrastructure such as drinking water, medical and healthcare servicesFurthermore, many respondents cited a lack of hope for improving living conditions as a reason for leaving the region. Out of 400 respondents, 384 (equivalent to 96%) identified economic factors as the primary cause of migration, while 256 (equivalent to 64%) reported to cultural and educational issues and the lack of a clear future outlook as their motivation for migrating.
Keywords: Samangan; economic factors; social factors; cultural factors; migration